(untitled) (Journal of Engineering, 2013)
This study focuses on the modeling of manufactured damper when used in steel buildings. The main aim of the manufactured dampers is to protect the steel buildings from the damaging effects that may result due to earthquakes by introducing an extra damping in addition to the traditional damping. Only Pure Manufactured Dampers, has been considered in this study. Viscous modeling of damping is generally preferred in structural engineering as it leads to a linear model then it has been used during this study to simulate the behavior of the Pure Manufactured Damper. After definition of structural parameters of a manufactured damper (its stiffness and its damping) it can be used as a structural element that can be added to a mathematical model of the structure. As the damping of manufactured dampers is generally greater than the damping of traditional materials, then the resulting damping matrix for the whole structure will be classified as a nonclassical damping. As most of literature on earthquake engineering have been written in terms of terminology related to mode superposition method and as this method is applicable to classical damping only. Then, this study tried to check the accuracy of the mode superposition method when applied to a structure with manufactured dampers. In this checking, approximated results of mode superposition method have been compared with more accurate results of direct integration method. From this comparison, it has been noted that the mode superposition method has different levels of accuracy depending on the relation between the fundamental frequency of the structure and the dominate frequency of the earthmotion. If the frequency of the structure is approaching to a dominate frequency of the earthmotion, then the damping effect will be important and the difference between the direct integration method and the model superposition method is increasing and vice versa